The Development and Use of a Novel Clinical Vignette as a Blended Learning Adjunct for Simulation-Based Learning During and Beyond COVID - Andrew Makkink (University of Johannesburg, 2022)
Case-based learning (CBL) is an important teaching tool for encouraging students to think as medical experts. Using blended learning principles to present a case where students can choose which information they require has the potential to improve learning where contact time is limited, as was the case during the COVID pandemic. This paper reports on a de novo online clinical vignette used as a foundation for a blended, case-based learning vignette that used follow-on Blackboard activities to improve teaching and learning. Student users were positive about the online CBL vignette and indicated that it provided several advantages to improved learning within the practical simulation environment, including improved confidence. In addition, integration with existing knowledge and other subjects was confirmed and immersion was improved. Benefits identified by student users included improved understanding of the real world of practice and encouraging thinking out of the box. There were suggestions that more multimedia would be a valuable improvement as well as students having access to additional similar activities. The implications of this research are that the online CBL vignette is a viable tool for enhancing blended learning within the practical, simulation-based teaching environment. More research is required on its applicability to other healthcare settings.